CHALLENGES IN SUSTAINABLE RESIDENTIAL PROPERTY DEVELOPMENT IN SHAH ALAM: PATHWAYS TOWARDS IMPLEMENTING SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Anis Syazwani Sukereman,; Mona Isa,; Khairul Anwar Abd Talif,; Nurul Nadiah Zainol,; Norhidayah Md. Yunus, (International Journal of Property Sciences (E-ISSN: 2229-8568), 2024)
There is an urgent need to align urban growth with environmental, social, and economic sustainability principles in rapidly developing cities like Shah Alam. The pressing issue is the current gap between the city's rapid development pace and its ability to implement sustainable practices that align with the SDGs. The study focuses on two main objectives: to identify potential pathways for implementing Sustainable Development Goals (SDGs) and challenges in residential property development in Shah Alam. By employing qualitative content analysis and purposive sampling, the research identifies critical challenges, including lack of awareness among buyers, high costs, inadequate government support, lack of expertise, strict regulations, longer procurement times, and a focus solely on achieving green certification. However, these obstacles also present opportunities for strategic pathways toward SDG implementation. The study emphasises that addressing these challenges and embracing these pathways can drive Shah Alam toward sustainable residential property development, contributing to the city's overall resilience and sustainability while aligning with crucial SDGs. This approach is crucial for alleviating poverty, enhancing urban sustainability, promoting resource efficiency, combating climate change, and protecting local ecosystems. By overcoming these challenges, Shah Alam can progress toward sustainable development that ensures long-term environmental, social, and economic benefits.